Pengaruh Gaya Hidup, Promosi, dan Harga terhadap iPhone pada iPhoneku Bandung Tulungagung - Diesta Wahyu Kusuma; Muhammad Alhada Fuadillah Habib (Journal of Management and Creative Business, 2024)
The iPhone smartphone is a smartphone brand from Apple that is currently in great demand by the public. From year to year, the iPhone has experienced developments in terms of its series and design which can attract consumer interest. One of the businesses that sells iPhones in Bandung, Tulungagung, is iPhoneku Bandung. iPhoneku Bandung is the only store that has the most consumers in the Bandung Tulungagung area. In the midst of a lot of competition for similar products, iPhoneku Bandung has managed to maintain its sales and become one of the choices for people around Bandung. This research aims to determine the influence of lifestyle, promotions and price on iPhoneku Bandung Tulungagung consumer purchasing decisions. The population in this research is iPhoneku Bandung consumers who have purchased iPhone products taken using accidental sampling technique. Samples were taken using the lemeshow formula so that a sample size of 100 respondents was obtained. Data collection was carried out using a questionnaire. The analytical method used in this research is multiple linear regression analysis with the help of the SPSS version 25 program.